2022
DOI: 10.1007/s10071-022-01602-y
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish excel in number discrimination under an operant conditioning paradigm

Abstract: Numerical discrimination is widespread in vertebrates, but this capacity varies enormously between the different species examined. The guppy (Poecilia reticulata), the only teleost examined following procedures that allow a comparison with the other vertebrates, outperforms amphibians, reptiles and many warm-blooded vertebrates, but it is unclear whether this is a feature shared with the other teleosts or represents a peculiarity of this species. We trained zebrafish (Danio rerio) to discriminate between numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 108 publications
5
14
0
Order By: Relevance
“…Initial trials did not distinguish between individual fish, although we observed considerable interindividual differences, consistent with the literature which finds that half 97 or even substantially more 109 individuals among zebrafish do not reach learning criteria for these tasks. The population trend was also compared with batch-specific results and no departure from population-level results were found (data not shown).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Initial trials did not distinguish between individual fish, although we observed considerable interindividual differences, consistent with the literature which finds that half 97 or even substantially more 109 individuals among zebrafish do not reach learning criteria for these tasks. The population trend was also compared with batch-specific results and no departure from population-level results were found (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…Therefore, in line with the literature 97,109 , significant associative learning does occur in this task among a subset (n=5) of fish tested (n=12), while the remaining fish tested showed freezing or frantic movement in response to the stimulus or considerable side bias in their responses within the first few days of training. Since all fish tested in this experiment were individually tracked, we could compare their side bias and WSLS score alongside their choices between the two visual stimuli (data for all five fish shown in Figure 5).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations